Identification of selection parameters for evaluating superior rice hybrids - Paul, A; Ahmad, Ekhlaque; Singh, D N; Singh, Munish Kumar (ORYZA-An International Journal of Rice, 2018)
Forty eight popular rice hybrids were studied to find out suitable genetic parameters for evaluation of an elite rice hybrid. The experiment was conducted during kharif 2012 and 2013 at Zonal Research Station, Chianki (Birsa Agricultural University, Ranchi), Palamau. A wide spectrum of variability was observed for all the characters in both the years. High genotypic coefficient of variation was observed for grains/panicle followed by test weight, grain yield and tillers/ plant both for the years. High heritability percent was observed for days to 50% flowering, test weight and grain yield during kharif, 2012 and 2013. Days to 50% flowering days to maturity, grains/ panicle and test weight had high positive significant association with grain yield whereas plant height, panicles/ sq. m and tillers/ plant showed positive significant correlation with grain yield at genotypic level. High positive direct effect was noted for test weight followed by grains/panicle, days to 50% flowering, days to maturity and plant height. Based on the results of the present study on correlation and path analysis, the characters i.e. grains/ panicle, test weight, days to 50% flowering and days to maturity influenced the grain yield either directly or indirectly in hybrid rice for improving the grain yield.